Application of experimental methods to improve student learning outcomes in single and mixed materials in elementary schools (Indonesian Institute for Counseling, Education and Theraphy, 2023)
This research is based on the researcher’s observation result in SD Budi Mulya that discovered many students are bored with the traditional speech method. Meanwhile, there has been many learning method’s inovations in science lesson, one of which is experimental method, which emphasized students to participate in teamwork, trying to prove the existed theories result through thorough procedures to gain a debatable/disscussable result. The objective of the research is to prove whether the application of experimental method in Science lesson on single and mixed substances could improve grade V students’ of SD Budi Mulya study result. This research is classroom action research (PTK) with data collection techniques, such as observation and tests. The students’ lesson result on first cycle was 75% and increased to 95%, there is 15% gap improvement. Nevertheless, teacher’s activity also has improvement in the quality and the effectiveness of learning process, started from 76,5% and ended at 90,5% on second cycle, with 14% differences from the beginning. With the increase of teachers’ activity percentage, automatically there were growth in students’ activity percentage from 62,5% on first cycle into 86,5% on second cycle, 24% improvemenet from the initial percentage